2021
DOI: 10.1038/s41525-021-00228-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of blood and bleeding disorder genes

Abstract: The advances and development of sequencing techniques and data analysis resulted in a pool of informative genetic data, that can be analyzed for informing decision making in designing national screening, prevention programs, and molecular diagnostic tests. The accumulation of molecular data from different populations widen the scope of utilization of this information. Bleeding disorders are a heterogeneous group of clinically overlapping disorders. We analyzed the targeted sequencing data from ~1285 Saudi indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The study could conclude that VWF levels are influenced by blood group and presence of certain gene variants indicating that both routine hematology testing and genetic analysis are important to decide on clinical management and classification of patients. 24–26 The results of the current study as well as other studies identified a few gene variants of VWF exon 18 that could be protective from VWD; therefore, individual’s genotyping is advocate to screen for high-risk group that allows early diagnosis and therapeutic intervention.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The study could conclude that VWF levels are influenced by blood group and presence of certain gene variants indicating that both routine hematology testing and genetic analysis are important to decide on clinical management and classification of patients. 24–26 The results of the current study as well as other studies identified a few gene variants of VWF exon 18 that could be protective from VWD; therefore, individual’s genotyping is advocate to screen for high-risk group that allows early diagnosis and therapeutic intervention.…”
Section: Discussionmentioning
confidence: 54%
“…VWF gene was observed with highest number of novel HGMD heterozygous variants among the blood and bleeding disorder genes reported from the Saudi population. 23 , 24 Further analysis of other exons in VWF gene in the study subjects can reveal the molecular basis of VWD.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular defects blood disorders, beta thalassemia, sickle cell disorder, alpha thalassemia and G6PD (Glucose-6-Phosphate Dehydrogenase) deficiency are the most common in the Arab population are extensively listed and reviewed earlier [1,[59][60][61][62][63]. The large-scale (~5000) WES analysis by the SHGP on the 1285 cases with 17 blood and bleeding disorders reveals more novel variants (n=140) than previously reported pathogenic variants (n=98) (Table 1) among the 821 variants [9]. VWF, F8, F5, G6PD, F2, F7, F10, F13B, FGA, and HBA2 genes observed with novel variants.…”
Section: Blood and Bleeding Disordermentioning
confidence: 96%
“…VWF , F8 , F5 , G6PD , F2 , F7 , F10 , F13B , FGA , and HBA2 genes were observed with novel variants. The authors prioritized the list of genes and novel variants in their study, which will definitely be a source of genetic data and will aid in the development of molecular variants’ screening and to enhance the efficiency of the preventive programs for the blood and bleeding disorders prevalent in the kingdom [ 9 ]. These molecular data will also have a significant impact on developing molecular diagnostic tools for the clinically overlapping disorders with blood and bleeding disorders and to design treatment strategies.…”
Section: Blood and Bleeding Disordersmentioning
confidence: 99%
See 1 more Smart Citation